2009
DOI: 10.1002/chin.200913164
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of New Substituted Azetidinoyl and Thiazolidinoyl‐1,3,4‐thiadiazino (6,5‐b) Indoles as Promising Antiinflammatory Agents.

Abstract: Synthesis of New Substituted Azetidinoyl and Thiazolidinoyl-1,3,4-thiadiazino (6,5-b) Indoles as Promising Antiinflammatory Agents. -3 Series of title of compounds of type (IX), (XI), and (XIII) (10 compounds each) are prepared and evaluated for their antiinflammatory, ulcerogenic, and analgesic effects. Compound (XIIId) possesses the best antiinflammatory and analgesic activities. -(BHATI, S. K.; KUMAR*, A.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Nonsteroidal anti-inflammatory drugs (NSAIDs) were widely used to treat acute and/or chronic inflammation due to their ability to relief symptomatic pain [1,2]. Conventional NSAIDs are non-selective cyclooxygenases (COX) enzyme inhibitors; they are involved in the biosynthesis of prostaglandin (PGs) from arachidonic acid [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs) were widely used to treat acute and/or chronic inflammation due to their ability to relief symptomatic pain [1,2]. Conventional NSAIDs are non-selective cyclooxygenases (COX) enzyme inhibitors; they are involved in the biosynthesis of prostaglandin (PGs) from arachidonic acid [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 1, 3, 4-thiadiazoles is a promising structure in medicinal chemistry and drug discovery [1] due to their diverse biological activities such as antihypertensive, anti-inflammatory, anti-bacterial, anti-amoebic [2], anti-HIV [3], antitumor and cytotoxic [4] activity. Moreover, they acts as a building block for the synthesis of various biologically active intermediates and derivatives [5,6]. Additionally, Schiff bases derived from amino-thiazoles have been shown to possess promising applications in various biological modeling and activities [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further, It is evident that the C=N linkage in azomethine derivatives is essential structure requirement for biological activity (Vinusha, 2015) such as, antimicrobial (da Silva et al, 2011), antibacterial (Vashi and Naik, 2004), anticancer (Kuz'min et al, 2005). It has been reported that indole and its derivatives are an important class of bioactive molecules in the field of drugs and pharmaceuticals areas including, anti-inflammatory (Sondhi et al, 2006, Bhati andKumar, 2008;Hemalatha et al, 2013), antimalarial (Santos, 2015, antimicrobial (Karekal et al, 2013;Bhaskar et al, 2007), antiviral (Tichý et al, 2012), antibacterial (Tiwari et al, 2006), antifungal (Guiqing et al, 2016), anticancer (Kumar and Kumer, 2013;Macdonough et al, 2013) and antioxidant activities (Estevão et al, 2010).…”
Section: Introductionmentioning
confidence: 99%